Body image concerns in men with localized prostate cancer - Peeters, Corien A (University of Ottawa (Canada), 2008)
It has been proposed that body image is an important aspect of quality of life that has received insufficient attention in research on medical populations (Pruzinsky & Cash, 2002). The present study was designed to assess the level of body image concerns in androgen-deprived and non-androgen deprived men undergoing radiation therapy for localized prostate cancer, and a comparison group of men without cancer. The relationship between body image concerns and quality of life, and the influences of disease-specific factors, physical functioning, and cognitive investment in appearance on body image was examined. 55 men receiving androgen deprivation therapy (ADT) and radiation therapy, 41 men receiving radiation only (RT), and 56 cancer-free men (CG) completed global and disease-specific measures of body image and quality of life. Only a minority of men with localized prostate cancer (13-30%) endorsed body image concerns above normative levels. After controlling for educational status, levels of body image concerns were comparable across the three groups. Higher levels of body image distress were associated with worse quality of life scores (mental health subscale, 36-item Short-Form Medical Outcomes Study Heath Survey); however, there was no group for whom this relationship was most salient. Despite ongoing interest in quality of life outcomes associated with ADT, findings from the present study suggest that ADT (for a minimum of 3 months) does not increase risk of body image concerns during radiation treatment. However, bother associated with hormone symptoms, as well as marital status, sexual functioning, perceived physical functioning, and cognitive investment in appearance were associated with body image concerns. Findings provided preliminary support for the cognitive-behavioural model of body image disturbance in cancer patients proposed by White (2000), such that cognitive investment in appearance predicted body image concerns above and beyond demographic, medical, sexual and physical functioning variables. By focusing on men receiving radiation therapy, including a comparison group, and including a comprehensive battery of disease-specific and theoretically-based body image measures, the present study addressed some of the gaps in the previous research. Findings suggest targeting several factors amenable to counselling or behavioural interventions, such as partner support, cognitive investment in appearance, and bother associated with ADT and physical functioning, to reduce body image concerns. Whereas diverse factors were relevant to body image concerns, findings showed that a specific focus on men's perceived physical functioning, and losing weight would likely improve body satisfaction in men undergoing treatment for localized prostate cancer.
Keywords: Psychology, Clinical.